Healthy Environmental Movement "Tree Planting In Coastal Areas," Dairi Regency, North Sumatra - Maryanti, Endang; Arifah, Rina; Amirah, Asriwati (Journal of Universal Community Empowerment Provision, 2025)
A healthy and sustainable environment is a fundamental need for the survival of humans and other living things. However, various human activities such as deforestation, pollution, and urbanization have threatened the balance of the ecosystem. Tree Plants will help in maintaining the balance of nature and the surrounding ecosystem so that it will reduce the Negative Impact on Human Health. This Community Service Activity aims to provide Education to the Community and support the preservation of Nature as a vital source in maintaining the balance of the ecosystem and a healthy quality of life. The implementation method is to use a collaborative and participatory approach, emphasizing the importance of the involvement of synergy of various resources, expertise and experience in overcoming complex problems found, collaboration is considered the key to producing better results by combining various perspectives and resources. Community Participation can directly meet the real needs of the Community in a sustainable manner. With good environmental management and the availability of natural resources, it can create a healthy quality of life and the sustainability of the ecosystem in the future.